2020
DOI: 10.1038/s41598-020-67830-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the continuous maize cultivation on soil properties in Sainyabuli province, Laos

Abstract: In tropical mountainous areas, soil degradation and yield decrease have been anticipated due to conversion from shifting to continuous cultivation and the introduction of cash crops. In our previous report, we quantified the decrease in maize yield under continuous cultivation in farmers’ fields in Laos. In this report, we focused on soil nutritional conditions under continuous cultivation in the farmers’ fields. For the purpose, twelve soil properties were investigated over two years from three sample sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Based on our study, we suggest that the lower levels of OM, TC, OC, and N-NO 3 observed in the F2 soils were due to intensive cultivation practices in the field, as continuous cultivation degrades the physicochemical properties of soils. These results coincide with those of Fujisao et al [62], who indicated that continuous cultivation under conventional tilling reduces the contents of TC, TN, and exchangeable K in maize soils. The lower OC in F2 soils may also explain the reason for the lower OM in the soils.…”
Section: Discussionsupporting
confidence: 92%
“…Based on our study, we suggest that the lower levels of OM, TC, OC, and N-NO 3 observed in the F2 soils were due to intensive cultivation practices in the field, as continuous cultivation degrades the physicochemical properties of soils. These results coincide with those of Fujisao et al [62], who indicated that continuous cultivation under conventional tilling reduces the contents of TC, TN, and exchangeable K in maize soils. The lower OC in F2 soils may also explain the reason for the lower OM in the soils.…”
Section: Discussionsupporting
confidence: 92%
“…Changere and Lal ( 1997 ) reported that sloping lands have disadvantages while flatlands are more suitable for maize growth. On the other hand, Fujisao et al ( 2020 ), reported that plant nutrients decreased in sloping lands where maize cultivation was carried out, and as a result, this limited the yield. The weighted value of the CaCO 3 parameter was determined as (0.065).…”
Section: Resultsmentioning
confidence: 99%
“…Pada lahan yang miring penanaman jagung secara terusmenerus menurunkan C organik, N total, P tersedia, K dan Ca dapat ditukar. Penurunan productivitas terjadi seiring dengan penurunan C organik tanah (Fujisao et al 2020).…”
Section: Pertanian Degeneratifunclassified